Evaluation of grain yields of selected bread wheat (triticum aestivum l.) Varieties in changing climatic conditions using different analytical models - Karaman, Mehmet (Bangladesh Journal of Botany, 2024)
In the present study were determined the variety or varieties with high grain yield and stability despite changing climatic conditions, and also to include these varieties as genetic material in parent lists in breeding programs. The additive main effect and multiplicative interaction (AMMI) analysis results the effects of cultivars (C), environments (E) and cultivar x environment interaction (CEI) were found to be important over grain yield at p≤0.01 level. Also, showed that grain yield performance of bread wheats were greatly affected firstly by the environment (70.42%), secondly from the interaction (7.29%), the least by variety (6.79%). The polygon graph obtained by genotype, genotype x environment (GGE) biplot analysis showed that two separate mega environments were formed, Nurkent variety was the best for first mega-environment, while Pehlivan variety for the second mega environment. GGE biplot determined that the ideal environment for bread wheat was environment 9 (E9) and the ideal genotype was Nurkent. Due to the visual presentation of AMMI and GGE biplot graphs, analysis results showed that these two models can be used to visually identify the best genotypes. Bangladesh J. Bot. 53(3): 545-554, 2024 (September)